Attributes of Women Leaders of State Colleges and Universities in Eastern Visayas, Philippines - Entoma, Susan S. (JPAIR Institutional Research, 2016)
Attributes of women come from their inner selves. These are both inherent and learned characteristics which are closely associated with their personal and professional well-being. The descriptive study supported by interview examined the attributes of women leaders about their leadership practices and their profile to develop a perceptual model for current and future women leaders of SUCs in Eastern Visayas, Philippines. The collected data from the 92 women leaders were analyzed and considered as the basis in the formulation of the perceptual model. Pearson- r was used to determine the correlation between the variables. The results showed that the prevailing personal attributes of women leaders are integrity, humility, and communication while empathy, self-evaluation, and time management are their professional attributes. These attributes are strongly influenced by their dominant leadership practices which are enabling others to act, modeling the way, and encouraging the heart. Women leaders’ age, educational attainment, academic rank, the number of years in a leadership position, and the number of leadership training attended indicated strong influence with the attributes. However, they will probably become effective in performing leadership tasks if they are strong in these aspects on attributes.